Posterior hip approach yields better functional results vis-à-vis anterolateral approach in total hip arthroplasty for patients with severe hip dysplasia: A prospective randomized controlled clinical study. (23rd June 2017) - Çatma, Faruk Mehmet; Öztürk, Alper; Ünlü, Serhan; Ersan, Önder; Altay, Murat
Objectives: We aimed to compare functional outcomes of two common hip approaches for patients with severe hip dysplasia in total hip replacement (THR) surgery. Materials and methods: Seventy hips of 68 patients randomized into two groups with regard to hip approach as posterior (group I) and anterolateral (group II). All patients underwent THR surgery with femoral shortening osteotomy. The groups were compared for operation time, preoperative and 6 months after abductor muscle strengths (AMSs), gait disorders, union time of the osteotomied site and dislocation rates. Results: There were two early dislocations in group I, and two early and one late dislocations in group II. No significant difference was observed regarding hip dislocations. Mean union time of the osteotomied site was 113.9 ± 51 days in group I while 111.1 ± 29.3 days in group II ( p = 0.774). Six months after surgery, group I had higher AMS than group II ( p < 0.0001). More patients in group II had Trendelenburg gait pattern ( p = 0.043), while no difference was observed regarding antalgic and deviated gait patterns between groups. Conclusion: THR surgery for patients with severe developmental dysplasia of hip is a challenging procedure, and posterior approach provides better functional outcomes regarding gait and AMSs.